2020
DOI: 10.3390/agronomy10091344
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Paraburkholderia phytofirmans PsJN Coated Diammonium Phosphate Enhanced Microbial Survival, Phosphorous Use Efficiency, and Production of Wheat

Abstract: Low bioavailability of phosphorus (P) in alkaline/calcareous soils leads to low yields due to its precipitation/fixation with calcium (Ca). An effective method to enhance phosphorus use efficiency (PUE) and its availability to plants is the application of alginate bioaugmented coated di-ammonium phosphate (DAP). In this study, the pre-isolated P solubilizing Paraburkholderia phytofirmans (PsJN) coated with different concentrations of polymer (alginate) on DAP with and without carbon source was tested in incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Moreover, as the P sources in the present study were bioaugmented with P-solubilizing microbes, these microbes might have enhanced indigenous and applied P solubilization through diverse mechanisms such as rhizospheric acidification and nutrient solubilization which in turn have improved plant growth and yield contributing factors in the present study. These results are in accordance with previously reported works [7,86].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Moreover, as the P sources in the present study were bioaugmented with P-solubilizing microbes, these microbes might have enhanced indigenous and applied P solubilization through diverse mechanisms such as rhizospheric acidification and nutrient solubilization which in turn have improved plant growth and yield contributing factors in the present study. These results are in accordance with previously reported works [7,86].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, in the present study, we found higher nutritional quality parameters of wheat grains under the combined application of P sources. This could be attributed to the presence of ammonium in DAP fertilizer which on hydrolysis might have caused acidification and resultantly enhanced solubility of bound P from Ca-P complexes [7]. The increased grain quality parameters in the present study may also be due to the enhanced supply of micronutrients such as Fe, Zn, Cu and Mn to wheat crop [98,99].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Therefore, a large amount of P recovery in struvite is particularly value added [4,13,14]. Additionally, struvite is also a comprehensive nutrient fertilizer and, as such, can promote the germination and growth of vegetables [15][16][17]. At present, commonly used nitrogen and phosphorus fertilizers, such as diammonium phosphate (46% P 2 O 5 , 18% N) and triple superphosphate (48% P 2 O 5 ), have similar nitrogen and phosphorus contents to struvite [13,18,19], which suggests that struvite could potentially be marketed as a fertilizer.…”
Section: Introductionmentioning
confidence: 99%